New York City Building, New York World's Fair 1939 (Grinnell Litho Co.)
Erected by the people of New York city, this building contains exhibits which acquaint the visitor with the various activities of the numerous departments of city government. The building, occupying a plt of 163,750 square feet, is to be permanent and after the Fair will be used as huge public sports palace.